2016
DOI: 10.1007/s13277-016-5111-1
|View full text |Cite
|
Sign up to set email alerts
|

INPP4B-mediated DNA repair pathway confers resistance to chemotherapy in acute myeloid leukemia

Abstract: INPP4B has been recently shown to be a poor prognostic marker and confer chemo- or radio-resistance in AML cells, whereas, the underlying mechanisms remain unclear. Herein, we aimed to explore the possible mechanisms mediated the resistance to chemotherapy in AML. We found that INPP4B-mediated resistance to genotoxic drug, cytarabine, was accompanied by lower p-H2AX accumulation in KG-1 cells, and INPP4B knockdown evidently sensitized KG-1 cells to cytarabine, meanwhile, p-H2AX expression was increased dramati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Compelling evidence has delineated the carcinogenesis of INPP4B in breast cancer [ 21 ], laryngeal cancer [ 22 ] and melanoma [ 23 ]. Recently, accumulating evidence has strongly implied that INPP4B served as independent prognostic marker and were associated with colony formation, proliferation and chemotherapy resistance in AML patients [ 24 26 ]. The previous research has elucidated that IRF2 elevated the activity of INPP4B promoter by directly binding to its promoter to increase INPP4B expression in AML cells [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence has delineated the carcinogenesis of INPP4B in breast cancer [ 21 ], laryngeal cancer [ 22 ] and melanoma [ 23 ]. Recently, accumulating evidence has strongly implied that INPP4B served as independent prognostic marker and were associated with colony formation, proliferation and chemotherapy resistance in AML patients [ 24 26 ]. The previous research has elucidated that IRF2 elevated the activity of INPP4B promoter by directly binding to its promoter to increase INPP4B expression in AML cells [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, that Inpp4a -/- MEF also displayed elevated pAkt levels compared to wild typ e after SV40 T-Large immortalization [46] support the notion that 4-phosphatase function is tumour suppressive in part through regulation of Akt signaling. Other mechanisms which have been linked to INPP4B loss include loss of ATM and ATR, both upstream regulators of the p53 pathway [22, 47] and INPP4B was reported to downregulate PTEN protein through its protein phosphatase activity [34]. Our efforts in this study demonstrated that p53 and Pten expression levels were unchanged between Inpp4b +/+ and Inpp4b -/- SV40 T-Large MEF (Figure 4B) indicating that these mechanisms may not be associated with the phenotypes we observed in MEF.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of INPP4B function is also highlighted in AML. Several studies have demonstrated increased INPP4B expression, which leads to chemotherapeutic resistance and poor patient outcomes [ 145 147 ]. Increased INPP4B expression was observed in a subset of AML cases associated with reduced therapeutic response, shorter event free and overall survival and was an independent biomarker of patient prognosis [ 145 , 146 ].…”
Section: Regulation Of Ptdins(345) P 3 mentioning
confidence: 99%
“…Induction of INPP4B in AML cells promoted cell proliferation, survival and desensitization to chemotherapeutic treatment in vivo and in vitro [ 145 , 146 ]. Conversely, siRNA knockdown of INPP4B sensitized AML cells to chemotherapeutic treatment, by inhibiting the activation of several DNA repair proteins including ATM and BRCA1 [ 147 ]. However, ectopic expression of a catalytically inactive INPP4B mutant yielded contrasting effects on the therapeutic response.…”
Section: Regulation Of Ptdins(345) P 3 mentioning
confidence: 99%